Critical Posthumanism and Cinema and Media Studies: The Italian Connection - Ferrara, Enrica Maria; Kilbourn, Russell J. A. (Quaderni d'Italianistica, 2025)
The first collection of articles solely dedicated to critical posthumanism in Italian Film, this special issue gathers a group of articles that explore the posthumanist dimension of Italian cinema and other audiovisual media, as a means of escaping a human-centred gaze and the Humanist—masculinist, patriarchal, colonialist, heteronormative—worldview it upholds. This critique takes a variety of unique forms in Italian screen media, inviting multiple theoretical approaches. The articles included in this special issue analyse through a posthumanist lens films by traditional auteurs, such as Dario Argento, Mario Bava, and Daniele Ciprì and Franco Maresco, but also by contemporary directors, such as Matteo Garrone and Pietro Marcello. As well as exploring the tropes and themes of posthumanist cinema, this collection aims to categorize the tools of a film language that gestures toward what was heretofore unavailable to physical, affective, or intellectual apprehension, and can be thought of productively in critical posthumanist terms.